Trustworthiness of digital government services: deriving a comprehensive theory through interpretive structural modelling. Issue 5 (4th May 2018) - Janssen, Marijn; Rana, Nripendra P.; Slade, Emma L.; Dwivedi, Yogesh K.
ABSTRACT: Having its origin in public administration, trustworthiness is a significant concept in digital government research, influencing the relationships between citizens and governments. However, the interrelationships between the facets of trustworthiness are given inadequate attention. Therefore, the aim of this research was to develop a theory detailing the factors affecting citizens' perceptions of e-government trustworthiness. A comprehensive review of public administration and information systems literature highlighted 20 pertinent variables. The interrelationships of these variables were identified and categorized according to their driving and dependence power by employing interpretive structural modelling. The proposed model was then drawn based on the level partitioning of variables and interrelationships of the variables determined using the final reachability matrix. The findings reveal that current conceptualizations of digital government trustworthiness take a too narrow view. The findings can help government policy makers with understanding the interrelated factors associated with trustworthiness in the context of digital government services and implement them in effective strategic planning.